Complementarities in capital formation and production: Tangible and intangible assets across Europe - Anna Thum-Thysen; Peter Voigt; Christoph Weiss (European Investment Bank (EIB), 2021)
This paper investigates capital formation with a view at various tangible and intangible assets across Europe. Using novel datasets both at macro and firm level, we estimate translog production functions to assess complementarities at different aggregation levels. At macro-level, our evidence suggests complementarities between tangibles and intangibles and between National Accounts and non-National Accounts intangibles. Using firm-level data, we explore more disaggregated asset classes and find that investing simultaneously in software, training of employees, and business process improvements is associated with better firm performance. Our analysis demonstrates that policy support that aims at stimulating investment only in certain assets may fall short in unlocking its own full potential. The emphasis should rather be on addressing investment bottlenecks arising from market imperfections, while remaining non-discriminatory with a view at what sort of capital deepening is envisaged and leaving it to the firm to find the most appropriate mix of assets.
Keywords: E01; E22; O34; O4; 330; intangible capital; asset complementarities; labour productivity; investment; innovation